SUMBANGSIH HASIL PENELITIAN DAN PENGEMBANGAN UNTUK INDONESIA LEBIH BAIK - Sabungan Sibarani (PROSIDING SEMINAR NASIONAL CENDEKIAWAN, 2019)
One form of evaluation that can be done to determine the contribution of an institution in conducting research activities is to measure the productivity of researchers through scientific publications. Publication productivity or also called research output or research productivity is one indicator of research performance or research performance. A researcher is said to have high productivity if many researchers produce scientific papers and are published in scientific journals. Contribution of research and development results is also intended for a better Indonesia. And without fail, it is also important to have input in making policies for publication of publications, as well as research planning, including providing the latest sources of information in research and development.